Huangqi Decoction Alleviates Alpha-Naphthylisothiocyanate Induced Intrahepatic Cholestasis by Reversing Disordered Bile Acid and Glutathione Homeostasis in Mice - Wu, Jia-Sheng; Li, Yi-Fei; Li, Yuan-Yuan; Dai, Yan; Li, Wen-Kai; Zheng, Min; Shi, Zheng-Chun; Shi, Rong; Wang, Tian-Ming; Ma, Bing-Liang; Liu, Ping; Ma, Yue-Ming (Frontiers in Pharmacology, 2017)
Intrahepatic cholestasis is a serious symptom of liver disorders with limited therapies. In this study, we investigated the efficacy of Huangqi decoction (HQD), a two-herb classic traditional Chinese medicine (TCM), in the treatment of alpha-naphthylisothiocyanate (ANIT)-induced intrahepatic cholestasis in mice. HQD treatment ameliorated impaired hepatic function and tissue damage. A metabolomics study revealed that the endogenous metabolites significantly affected by HQD were related to bile acid (BA) biosynthesis and glutathione metabolism pathways. HQD treatment decreased the intrahepatic accumulation of cytotoxic BAs, normalized serum BA levels, and increased biliary and urinary BA excretion. Additionally, HQD restored the hepatic glutathione content and suppressed reactive oxygen species (ROS) in cholestatic mice. Protein and gene analysis revealed that HQD increased the expression of the hepatic metabolizing enzymes cytochrome P450 (CYP) 2B10 and UDP glucuronosyltransferase family 1 member A1 (UGT1A1), as well as multidrug resistance-associated protein 2 (Mrp2), Mrp3, and Mrp4, which play crucial roles in BA homeostasis. Further, HQD increased the protein expression of glutamate-cysteine ligase, which is involved in the synthesis of glutathione. Importantly, HQD increased the nuclear expression of nuclear factor-E2-related factor-2 (Nrf2). In conclusion, HQD protects against intrahepatic cholestasis by reversing the disordered homeostasis of BAs and glutathione.